2018
DOI: 10.1590/0103-1104201811615
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da satisfação dos usuários atendidos por serviço pré-hospitalar móvel de urgência

Abstract: The aim of this study was to evaluate the satisfaction of the users assisted by the Mobile Emergency Care Service of the state of Rio Grande do Norte. It is a transversal, analytical and quantitative research, carried out from January to June of 2016, with 384 users. Satisfaction was obtained in structure and process. The indicator of structure that generated more dissatisfaction was the comfort of ambulances, and of the process was the response time. It is concluded that users are, mostly, satisfied with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
2
6
0
2
Order By: Relevance
“…In line with the findings of the present study, research by Johansson et al in Sweden suggested favorable levels of satisfaction of patients with pre-hospital emergency services [13]. Various domestic and international studies also indicated overall satisfaction with the desired level of emergency services [10,12,[14][15][16][17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In line with the findings of the present study, research by Johansson et al in Sweden suggested favorable levels of satisfaction of patients with pre-hospital emergency services [13]. Various domestic and international studies also indicated overall satisfaction with the desired level of emergency services [10,12,[14][15][16][17].…”
Section: Discussionsupporting
confidence: 88%
“…Besides, resolving the problems regarding equipment shortages of emergency ambulances is of significant importance. Most studies have revealed that patient satisfaction is a useful indicator for estimating the quality of medical care [12,14,15,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para averiguar os indicadores que refletem em um atendimento de êxito e qualidade, são observados pelo paciente: tipo de atendimento dado pela equipe, relacionamento interpessoal, habilidade técnica, disponibilidade de materiais e tempo de atendimento entre outros, pois tais aspectos são indispensáveis para a qualidade do atendimento ofertado (6) .…”
Section: Discussionunclassified
“…Entretanto, tem sido um desafio a identificação dos indicadores viáveis e válidos nos serviços pré-hospitalar, pois as publicações atuais são escassas (5) . Destaca-se que um compilado dos indicadores de qualidade, relacionados à avaliação dos serviços pré-hospitalares, facilitaria o gerenciamento destes serviços e a implantação de estratégias assertivas que busquem melhoria da qualidade e da segurança neste processo de trabalho (6) .…”
Section: Introductionunclassified